2019
DOI: 10.1177/2381468319866448
|View full text |Cite
|
Sign up to set email alerts
|

Operative Versus Nonoperative Management of Appendicitis: A Long-Term Cost Effectiveness Analysis

Abstract: Background. Recent clinical trials suggest that nonoperative management (NOM) of patients with acute, uncomplicated appendicitis is an acceptable alternative to surgery. However, limited data exist comparing the long-term cost-effectiveness of nonoperative treatment strategies. Design. We constructed a Markov model comparing the cost-effectiveness of three treatment strategies for uncomplicated appendicitis: 1) laparoscopic appendectomy, 2) inpatient NOM, and 3) outpatient NOM. The model assessed lifetime cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
1
12
0
1
Order By: Relevance
“…Sceats et al . revealed that NOM was associated with higher abscess rates, readmission, and higher overall care costs [ 54 ]. As long as the appendix remains, the risk of recurrence is latent.…”
Section: Discussionmentioning
confidence: 99%
“…Sceats et al . revealed that NOM was associated with higher abscess rates, readmission, and higher overall care costs [ 54 ]. As long as the appendix remains, the risk of recurrence is latent.…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, almost 10% might recur with complicated appendicitis, which implies higher costs subsequently. Sceats et al revealed that NOM was associated with higher abscess rates, readmission, and higher overall care costs (37). As long as the appendix remains, the risk of recurrence is latent.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors can advance or postpone the TTA for patients with acute uncomplicated appendicitis and acute comorbid appendicitis according to the patient's urgency and through communication and negotiation. Surgery should be scheduled during the day on weekdays, which will help improve the utilization and effectiveness of hospitals' medical resources and reduce medical expenses [52,53]. Prior studies demonstrated that the readmission rate after appendectomy is estimated to be between 1% and 19% [54,55,56], which showed that improving the e ciency of diagnosis and timely management, especially the value of nursing care, is bene cial to hospitals [57].…”
Section: The In Uence Of Other Factors On Hospitalization Expensesmentioning
confidence: 99%